Unlocking the Mechanisms of Hidradenitis Suppurativa: Inflammation and miRNA Insights - Ames E; Sanders M; Jacobs M; Vida TA (Clinical, Cosmetic and Investigational Dermatology)
Emily Ames, Maggie Sanders,* Marley Jacobs,* Thomas A Vida Department of Medical Education, Kirk Kerkorian School of Medicine at UNLV, Las Vegas, NV, USA*These authors contributed equally to this workCorrespondence: Thomas A Vida, Department of Medical Education, Kirk Kerkorian School of Medicine at UNLV, 625 Shadow Ln, Las Vegas, NV, 89106, USA, Email thomas.vida@unlv.eduAbstract: Inflammatory skin diseases impose a significant burden on patients and healthcare systems worldwide. Among these, hidradenitis suppurativa (HS) is particularly notable for its chronic and recurrent nature. Recurrent nodules, abscesses, and scarring in apocrine gland-rich areas characterize the disease, including the groin, axillae, and perianal regions. Despite its considerable physical and psychological impact, the precise mechanisms driving HS remain elusive. Recent advancements in understanding the inflammatory processes involved in HS have highlighted the TNF-alpha, IL-1β, and IL-17/IL-23 pathways, which play crucial roles in initiating and perpetuating the disease. Moreover, specific microRNAs (miRNAs), such as miR-24-1-5p, miR146a-5p, mirR-26a-5p, miR-206, miR-338-3p, and miR-338-5p, are involved in these inflammatory processes. Dysregulation of these miRNAs contributes to aberrant cytokine expression and persistent inflammation, foreseeably exacerbating HS disease progression. This narrative review hypothesizes that miRNA dysregulation triggers aberrant expression in specific inflammatory pathways, contributing to HS’s clinical manifestations and progression. We explore the implicated miRNAs’ potential as biomarkers for earlier disease detection and as novel therapeutic targets. Identifying miRNA dysregulation offers new opportunities for earlier and more accurate diagnosis, potentially allowing clinicians to intervene before severe disease manifestations occur. Furthermore, therapeutic strategies to modulate miRNA expression could target the inflammatory pathways driving HS, leading to more personalized and effective treatments. This review also discusses future research directions to enhance the clinical management of HS. A better understanding of miRNA involvement in HS offers new avenues for research and management, ultimately improving patient outcomes and quality of life.Keywords: chronic inflammation, sebaceous glands, inflammatory pathways, immunosuppressant drugs, miRNA dysregulation